The impact of a local supply chain strategy on regional economic - Tatiana A. Evstratova; Elena E. Kabanova; Ekaterina A. Vetrova; Polina V. Palehova; Irina A. Duborkina (International Journal of Supply Chain Management, 2020)
Abstract- The aim of this research is to explore socio-economic risks and challenges, in the modern globalized production landscape from an end-to-end supply chain perspective. Given the sensitivity of a Russian regional economy contribution to its supply chains, any improvement in supply chains strategy will be beneficial for mines and their stakeholders. The objectives of this work were to: (i) test the hypothesis that supply chain management strategy, by mines in a region, significantly affects regional economy; and (ii) develop a methodology to identify the critical backward commodities of a regional economic sector. The complexity of the strategic development of the region is conditioned by the fact that it is necessary to take into account the characteristics of all cities and settlements, to be able to integrate their plans into a single document, which allows to build a single development strategy for the entire territory. The development of a regional development strategy is the most important task of both regional science and the practical activities of regional authorities. The relevance of the study concerning the processes and tools of strategic planning for the development of Russian Federation constituent entities is conditioned by the fact that the quality of strategic documents that determines the success of the territory development in modern, dynamically developing socio-economic conditions. At present, the main agency responsible for the strategic approach to the development of the territory is the Ministry of Economic Development of the corresponding territory, which, in conjunction with the regional government, other ministries and departments, forms a document defining the main development vectors of the Russian Federation constituent entity, and the Ministry is responsible for the quality of this document. Orientation to the strengths or weaknesses of the region can act as the principles for the regional development strategy creation, and the content of the strategy determines which sectors will be priority in terms of their development support, which will be provided with additional sources of financing, and which will be developed independently, without state close attention.